Determinan Intensi Berwirausaha Mahasiswa Pascasarjana Ipb Pada Bidang Agribisnis - Dani Arisandi; Rachmat Pambudi; Ratna Winandi Asmarantaka; Wahyu Kumala Sari (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2023)
Increasing of population impacted to food needs and unemployment problem. so there is a solution to resolve with entrepreneurship. The aims of this study is to look the characteristics of respondents and the factors that influence the entrepreneurial intention of student at the Postgraduate School of Bogor Agricultural University (SPs-IPB) on agribusiness. The design of this study used cross sectional study. Respondent in this study are postgraduate student from magister program. The sampling technique used proportional stratified random sampling with 122 people. The analytical method used descriptive quantitative analysis and Structural Equation Modelling / SEM. The results showed that as (94%) of respondents have entrepreneurial intentions generally, (86.96%) of the respondents have the intention of entrepreneurship in agribusiness. The study found that entrepreneurial intention are influenced by subjective norm which is the influence of a number of parties that are considered important with regard to the behavior of entrepreneurs.